Discriminatory suppression of homologous recombination by p53 - Yun, Sheng (Oxford University Press, 2004)
Homologous recombination (HR) is used in vertebrate somatic cells for essential, RAD51-dependent, repair of DNA double-strand-breaks (DSBs), but inappropriate HR can cause genome instability. A transcriptional transactivation-independent role for p53 in suppressing HR has been established, but is not detected in all HR assays. To address the basis of such exceptions, and the possibility that suppression by p53 may be discriminatory, we have conducted a controlled comparison of the effects of p53 depletion on three different kinds of HR. We show that, within the same cells, p53 depletion promotes both intra-chromosomal HR (ICHR) and extra-chromosomal HR (ECHR), but not homologous DNA integration (gene targeting; GT). This conclusion holds true for both spontaneous and DSB-induced ICHR and GT. We show further that non-conservative ICHR is more susceptible than conservative ICHR to inhibition by p53. These results provide strong evidence that p53 can discriminate between different forms of HR and, despite the fact that GT is used experimentally for gene disruption, is consistent with the possibility that p53 preferentially suppresses genome-destabilizing forms of HR. While the mechanism of suppression by p53 remains unclear, our data suggest that it is independent of mismatch repair and of changes in RAD51 protein levels.